2011
DOI: 10.1310/hct1202-71
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Complete Adherence to HIV Combination Antiretroviral Therapy

Abstract: This study shows the negative impact of higher pill burden on medication adherence, an important factor associated with treatment outcomes in patients with HIV/AIDS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 17 publications
4
37
0
Order By: Relevance
“…Similar to previous studies,4 20 we found that patients who were adherent to therapy were less likely to be hospitalised. Our data demonstrated similar rates of hospitalisations among patients with the highest levels of complete adherence—at least 95%.…”
Section: Discussionsupporting
confidence: 90%
“…Similar to previous studies,4 20 we found that patients who were adherent to therapy were less likely to be hospitalised. Our data demonstrated similar rates of hospitalisations among patients with the highest levels of complete adherence—at least 95%.…”
Section: Discussionsupporting
confidence: 90%
“…Although these studies were not included, the general trend of these adherence results was consistent with those of the present analysis. Furthermore, the present results of better adherence and efficacy with fixed-dose combination therapy are supported by results from other therapeutic classes including antihypertensive agents, antiretroviral therapies for HIV, and lipid-modifying therapies [37][38][39] .…”
Section: Discussionmentioning
confidence: 60%
“…Fielden et al 18 and Juday et al 19 have found that adherence is a key factor in decreasing the risk of hospitalisation. In this study poor adherence to antiretroviral treatment was not an independent predictor.…”
Section: Discussionmentioning
confidence: 99%